Network function virtualization fault analysis and processing method based on improved intelligent optimization algorithm - Zhiming WANG; Bing CHEN (Dianxin kexue)
Network function virtualization has become an important trend in the global development of telecommunications industry，with the rapid development of network function virtualization and rapid growth of the telecommunications business，analysis and processing of data is too large to deal with，its problems such as low efficiency of fault analysis and processing have become increasingly prominent.For the increasingly urgent development needs of network function virtualization，fault analysis and processing method based on improved intelligent optimization algorithm is important for the rapid and sustainable development of network function virtualization.Based on the research of the convention mechanism of fault analysis and processing for network function virtualization，a method of fault analysis and processing for network function virtualization based on improved intelligent optimization algorithm was presented，it could solve the existing problems of fault analysis and processing for network function virtualization better.